2014
DOI: 10.4308/hjb.21.4.173
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Akt and p53 Protein Expression and Chemoradiotherapy Response in Cervical Cancer Patients

Abstract: Akt is a protein that is associated with cell proliferation and is expressed at high levels in cancer cells. Some research indicates it may play a role in increasing the resistance of cancer cells to chemotherapy treatment. P53 is a tumor suppressor protein that influences the cell cycle and apoptosis. The purpose of this study was to examine the relationship between the expression of Akt and p53 in cancerous tissue before chemoradiation treatment, and the clinical response to treatment of cervical cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70] The overexpression of Akt1 and EGFR is associated with the poor survival and clinical outcomes of patients with CC. 69,71 The oncogene JUN is upregulated in the CC tumor tissues compared to normal tissues, and lower JUN expression is related to higher survival among patients with CC. 72 The estrogen receptor α (encoded by ESR1) is associated with the tumorigenesis, development, and persistence of CC.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70] The overexpression of Akt1 and EGFR is associated with the poor survival and clinical outcomes of patients with CC. 69,71 The oncogene JUN is upregulated in the CC tumor tissues compared to normal tissues, and lower JUN expression is related to higher survival among patients with CC. 72 The estrogen receptor α (encoded by ESR1) is associated with the tumorigenesis, development, and persistence of CC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that PI3K/AKT activity was elevated in the cells harboring high levels of tP53 mutant protein [28][29][30], and more than half of the solid tumors harbor mutated tP53 protein that suppresses autophagy and ceases cancer cell apoptosis [31][32][33]. On the other side, it has been reported that suppression of autophagy by PI3K/AKT activation accelerates tumor growth due to inflammation [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the high level of Akt indicated poor radiotherapy response, and there were no association between some proliferation markers like AgNOR, MIB-1, and p53 with radiotherapy response [13,14]. The aim of the present study is to investigate the relationship between p70s6k as biomarker and radiotherapy response in cervical cancer.…”
mentioning
confidence: 99%